Economía circular del cultivo de cacao (Theobroma cacao L.) en la provincia de los Ríos - Chesme Rios Carolina Liseth, Chesme Rios Carolina Liseth (2023)
The inadequate management of residues from the harvest and agricultural production, has generated great environmental problems that emerge to the population and the ecosystem. The present investigation was carried out in the North Zone of the Los Ríos Province, in order to analyze circular economy alternatives that reduced the contamination caused by the production of the cocoa crop (Theobroma cacao L.) in the study area. For which a simple random test was carried out with a confidence level of 95% and 0.05 error, obtaining a sample of 372 agricultural production units, after which a stratified test was used to know the number of surveys to be applied in each case. each of the cantons, to collect the information, the survey with open and closed questions was obtained as an instrument, for the analysis the chi-square test was used with the purpose of knowing the relationship between the variables, it should be emphasized that a descriptive research. The review of 50 scientific articles will be modified to take advantage of cocoa by-products in 20 different ways in nine areas, 86% of farmers are interested in taking advantage of their residues to make chocolate, the chi-square revealed that between the canton vs assistance variables technique and level of education received vs knowledge about the circular economy if there are significant statistical differences, 54 potential benefits of the circular economy were determined, 24 environmental, 17 social and 13 economic, highlighting among them the reduction of climate change, greater economic stability and improvement in health. Nine circular economy alternatives suitable for the study area were proposed, with an affordable cost. The potential that exists in the study area to take advantage of cocoa by-products is evident; farmers, by implementing the actions presented, could improve positively. Keywords: Waste utilization, recovery of by-products, cocoa circularity, waste potential, benefits of circularity